The Role of Cybersecurity and Risk Management in E-Commerce from Customers' Perspective - Turki Ahmed Daifallah Al-Awaji (International Journal of Computers and Informatics, 2024)
One of the most important types of risks in e-commerce is cybersecurity. With the increasing number of cyber-attacks and data breaches, it has become necessary for companies to protect their information and their customers' information from theft or loss. Cyber-attacks can cause huge financial losses and damage the company's reputation. The problem with the study lies in the gap in understanding how e-commerce risk management affects consumer behavior and satisfaction. Companies need effective risk management strategies to maintain customer satisfaction and ensure the continuity of business operations.
Keywords: Cybersecurity; Risk Management; E-Commerce